Numerical Investigation Of Free Convection Over A Permeable Horizontal Flat Plate Embedded In A Porous Medium With Radiation Effects And Mixed Thermal Boundary Conditions - Mohd Zuki, Salleh; Najihah, Mohamed; Rozieana, Khairuddin; Najiyah Safwa, Khasi’ie; Roslinda, Nazar (2010)
In this paper, the mathematical modelling of free convection boundary layer flow over a permeable horizontal flat plate embedded in a porous medium under mixed thermal boundary conditions and radiation effects, is considered. The transformed boundary layer equations are solved numerically using the shooting method. Numerical solutions are obtained for the wall temperature, the heat transfer coefficient, as well as the velocity and temperature profiles. The features of the flow and heat transfer characteristics for different values of the radiation parameter , R N the mixed thermal boundary condition parameter